A voice pitch indicator for training deaf scholars - Anderson, Fred (Department of Electrical Engineering, 2016)
The instrument to be described, is based on experimental work documented by the author in 1960 and was developed specifically as a teaching aid to be used in the speech training of deaf scholars. The only natural means by which a completely deaf child can compare his own speech with that of his teacher, is by observation of lip and facial movements and by feeling the vibrations of the vocal organs. Hence he is using the senses of sight and touch neither of which is capable of passing sufficient information to allow the child to develop good voice intelligibility. Two properties of speech which contribute significantly to intelligibility are pitch and stress, and since these are relatively slowly varying quantities, the sense of sight can readily be trained to receive and process this information if presented to it in suitable form. In this instrument, pitch or amplitude information is displayed as the ordinate of a graph, the abscissa of which is time. A continuous time-base is obtained by rotating a cathode-ray-tube with a long-persistence screen inside a stationary deflecting coil. The patterns thus formed, remain visible for a sufficient length of time for detailed interpretation by the sense of sight. Pitch information is derived from measurements performed on the waveform of the speech signal, a process which unavoidably leads to errors. A system for detecting and eliminating these errors is described. The application of the instrument, which has been used successfully over an extended period of time, is described briefly.